Workshop Teknik Penulisan Soal Berbasis Kurikulum Merdeka bagi Guru SD Negeri 49 Bombana - Ahmad Ahmad; Sri Marlia Putri; Ashari Usman (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
The Independent Curriculum requires teachers to have skills in compiling questions that not only measure students' understanding, but also critical and creative thinking skills. This workshop aims to improve the competence of elementary school teachers in compiling questions based on the Independent Curriculum that are in accordance with the principles of formative and summative assessment. This activity is carried out through direct training involving the delivery of materials, practice of compiling questions, and joint discussion and reflection. The evaluation results show that after attending the workshop, teachers experienced an increase in understanding good question structures, were able to differentiate cognitive levels in compiling questions, and were more confident in compiling assessment instruments. This workshop is expected to be the first step in improving the quality of learning evaluation in elementary schools.